Answer:
Aaron = 54
Bola = 18
Step-by-step explanation:
Let
[tex]A \to Aaron[/tex]
[tex]B \to Bola[/tex]
From the first statement, we have:
[tex]A = 3B[/tex]
After given Bola 6 sweets,
[tex]A - 6 = 2(B + 6)[/tex]
Required
The initial number of sweets each has
Substitute [tex]A = 3B[/tex] in [tex]A - 6 = 2(B + 6)[/tex]
[tex]3B - 6 = 2(B + 6)[/tex]
Open bracket
[tex]3B - 6 = 2B + 12[/tex]
Collect like terms
[tex]3B -2B = 12+6[/tex]
[tex]B = 18[/tex]
Substitute [tex]B = 18[/tex] in [tex]A = 3B[/tex]
[tex]A = 3 * 18[/tex]
[tex]A = 54[/tex]